Measuring gas hold‐up in gas–liquid/gas–solid–liquid stirred tanks with an electrical resistance tomography linear probe. Issue 6 (8th March 2019) - Forte, Giuseppe; Alberini, Federico; Simmons, Mark J. H.; Stitt, E. Hugh
Abstract: An electrical resistance tomography (ERT) linear probe was used to measure gas hold‐up in a two‐phase (gas–liquid) and three phase (gas–solid–liquid) stirred‐tank system equipped with a Rushton turbine. The ERT linear probe was chosen rather than the more commonly used ring cage geometry to achieve higher resolution in the axial direction as well as its potential for use on manufacturing plant. Gas‐phase distribution was measured as a function of flow regime by varying both impeller speed and gas flow rate. Global and local gas hold‐up values were calculated using ERT data by applying Maxwell's equation for conduction through heterogeneous media. The results were compared with correlations, hard‐field tomography data, and computational fluid dynamic simulations available in the literature, showing good agreement. This study thus demonstrates the capability of ERT using a linear probe to offer, besides qualitative tomographic images, reliable quantitative data regarding phase distribution in gas–liquid systems.